Substructure analysis of the RXCJ0232.2–4420 galaxy cluster. Issue 1 (22nd March 2021) - Parekh, Viral; Laganá, Tatiana F; Kale, Ruta
ABSTRACT: RXCJ0232.2–4420, at z  = 0.28, is a peculiar system hosting a radio halo source around the cool-core of the cluster. To investigate its formation and nature, we used archival Chandra and XMM – Newton X-ray data to study the dynamical state of the cluster and detect possible substructures in the hot gas. Its X-ray surface brightness distribution shows no clear disruption except an elongation in the north-east to south-west direction. We perform the unsharp masking technique and compute morphology parameters (Gini, M 20, and concentration) to characterize the degree of disturbance in the projected X-ray emission. Both of these methods revealed a substructure, which is located at ∼1 arcmin from the cluster core in the south-west direction. Previous spectral analysis conducted for RXCJ0232.2–04420 concluded that there are a short cooling time and low entropy at the cluster centre, indicating that the cluster has a cool core. Thus, we suggest that RXCJ0232.2–4420 may be a system where the core of the cluster is not showing any sign of disturbance, but the south-west substructure could be pumping energy to the detected radio halo via turbulence.